Espessura da zona de transição do manto sob a Província Borborema, NE Brasil, através de conversões Ps telessísmicas - Pinheiro, Adriane Gomes (2014)
The mantle transition zone is defined by two seismic discontinuities, nominally at 410 and 660 km depth, which result from transformations in the mineral olivine. The topography of these discontinuities provides information about lateral temperature changes in the transition zone. In this work, P-to-S conversions from teleseismic events recorded at 32 broadband stations in the Borborema Province were used to determine the transition zone thickness beneath this region and to investigate whether there are lateral temperature changes within this depth range. For this analysis, stacking and migration of receiver functions was performed. In the Borborema Province, geophysical studies have revealed a geoid anomaly which could reflect the presence of a thermal anomaly related to the origin of intraplate volcanism and uplift that marked the evolution of the Province in the Cenozoic. Several models have been proposed to explain these phenomena, which include those invoking the presence of a deep-seated mantle plume and those invoking shallower sources, such as small-scale convection cells. The results of this work show that no thermal anomalies are present at transition zone depths, as significant variations in the transition zone thickness were not observed. However, regions of depressed topography for both discontinuities (410 and 660 km) that approximately overlap in space were identified, suggesting that lower-thanaverage, lateral variations in seismic velocity above 410 km depth may exist below the the Borborema Province. This is consistent with the presence of a thermally-induced, low-density body independently inferred from analysis of geoid anomalies. Therefore, the magma source responsible for the Cenozoic intraplate volcanism and related uplift in the Province, is likely to be confined above the upper mantle transition zone.